Síntese de compostos N-heterocíclicos via fotocatálise - Souza, Wanderson Costa de (Universidade Federal de São Carlos, 2022)
Heterocycles belong to a privileged class of organic compounds that play a prominent role in chemistry and biology. There is an extensive literature about methodologies for the synthesis of these substances, showing their importance. In the last decade, photocatalysis has undergone a substantial expansion driven by the search for new ways to achieve molecule activation and the growing interest in the development of more sustainable methodologies. In view of this scenario, our group has sought to contribute to the progress of photocatalyzed methodologies, applying photocatalysis to synthesize N-heterocyclic compounds. In this study, three photocatalytic methodologies were developed, one employing photoredox catalysis and the others employing photocatalysis by energy transfer. The first one is described as a cascade cyclization reaction initiated by alkyl radicals generated via photocatalyzed deamination by visible light. Under mild reaction conditions, the developed method provides a series of benzazepinones with a wide substrate scope, good functional group tolerance and good yields. In the second methodology, the synthesis of cyclobutanequinolinones was achieved through [2+2] cycloaddition reactions by energy transfer. The method has also a wide substrate scope, tolerates structural variations well and produces a large variety of cyclobutane derivatives with yields ranging from 27-99%, and with excellent regio- and diastereoselectivity. The third methodology was developed using 1,3-enynes in photocatalyzed reactions. It is a highly sustainable methodology which employs a metal-free catalyst (1,2,3,5-tetrakis(carbazol-9-yl)-4,6-dicyanobenzene) (4CzIPN), blue LED as activation source and a dimethylcarbonate solvent. (DMC). By this method, a series of 1,3-diene quinolinone derivatives were obtained in excellent yields.
Synthesis of N-heterocyclic compounds via photocatalysis
Keywords: Fotocatalise; N-heterociclicos; CIENCIAS EXATAS E DA TERRA::QUIMICA